2010
DOI: 10.3324/haematol.2010.023713
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase enhances the generation of activated factor X in the presence of tissue factor and activated factor VII

Abstract: BackgroundHeparanase is an endo-β-D-glucuronidase dominantly involved in tumor metastasis and angiogenesis. Recently, we demonstrated that heparanase is involved in the regulation of the hemostatic system. Our hypothesis was that heparanase is directly involved in activation of the coagulation cascade. Design and MethodsActivated factor X and thrombin were studied using chromogenic assays, immunoblotting and thromboelastography. Heparanase levels were measured by enzyme-linked immunosorbent assay. A potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 32 publications
4
73
0
1
Order By: Relevance
“…In line with our previous findings, 24,25 endothelial heparanase overexpression observed in aged mice was paralleled by elevated plasma factor Xa activity levels. Moreover, transgenic mice overexpressing human heparanase exhibited shortened time to arterial thrombosis following vascular injury and increased in-stent thrombosis.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In line with our previous findings, 24,25 endothelial heparanase overexpression observed in aged mice was paralleled by elevated plasma factor Xa activity levels. Moreover, transgenic mice overexpressing human heparanase exhibited shortened time to arterial thrombosis following vascular injury and increased in-stent thrombosis.…”
Section: Discussionsupporting
confidence: 80%
“…Aged End.p53-WT mice exhibited significantly higher plasma factor Xa levels compared with their adult counterparts, whereas a similar age-dependent increase was not observed in End.p53-KO mice ( Figure 4A). In line with the role of heparanase in factor X activation, as previously shown by our group, 24,25 western blot analysis revealed significantly increased heparanase expression in primary endothelial cells isolated from lungs of aged compared with adult WT mice ( Figure 4B; representative western blot findings in Figure 4E). Protein levels of Egr1, involved in the transcriptional regulation of p53 26 and heparanase, 27,28 also were higher in endothelial cells of aged mice ( Figure 4C,E).…”
Section: Deletion Of P53 In Endothelial Cells Protects Aged Mice Agaisupporting
confidence: 62%
“…However, enzymatically inactive heparanase (proenzyme) did not have an effect on heparanase-activated partial pro-thrombin time or platelet aggregation. Recent reports have also suggested that heparanase may act through alteration of TF and activated factor X (24,25). Together these results suggest that heparanase has only a moderate effect on the hypercoagulability of the blood (overexpression of TF with compensation by TF pathway inhibitor).…”
Section: Discussionmentioning
confidence: 99%
“…Up-regulation of TF adds another example of the multiple non-enzymatic functions of heparanase. Recently, we have demonstrated that heparanase may serve as a cofactor of TF, suggesting that heparanase is directly involved in activation of the coagulation cascade 17. The findings were supported by experiments indicating that heparanase increases the level of factor Xa in the presence of TF/VIIa and the effect is enzymatically independent.…”
Section: Heparanase As a Cofactor To Tissue Factor Activitymentioning
confidence: 57%
“…Heparanase was recently revealed as an important modulator of blood coagulation 13,17,18,27. Generating peptides inhibiting heparanase procoagulant activity36 strengthens the role of heparanase as a new procoagulant factor in the coagulation cascade.…”
Section: Resultsmentioning
confidence: 98%